PERANAN PPAT DALAM ALIH FUNGSI LAHAN PERTANIAN KE NON PERTANIAN DI KABUPATEN BANTUL - , DWI ANDRI AFIANI, Prof. Dr. Sudjito, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This risearch aimed to conversion of the agricultural land area into the nonagricultural public beliaved to Land Deed Official, to undestand law constuction between public and Land Deed Official to conversion of the agricultural land area into the non-agricultural, and undestand factor-factor distrub Land Deed Official conversion of the agricultural land area into the non-agricultural. This research is juridical-sociological study, namely, a study conducted by field research to collect primary data. Subjects of research were determined by non random sampling and samples were taken by using purposive sampling method. Data were collected by interview. To complete the primary data, a literature study was conducted to obtain secondary data. From the collected primary and secondary data, then these data were analyzed qualitative and presented in descriptive form. The result shows the involvement of Land Deed Official on land conversion in Bantul District has broad meaning, as well as land conversion that means alteration process from farmland to non farmland. Land Deed Official conducting drainage service for the people means alteration license from farmland to non farmland, or generally called land function allotment conversion or land status allotment conversion. The Goverment Regulation Article 7 Number 37 of 1998 on The Regulation of Land Deep Official, it stated that